Suicide as a Weapon - Centre, of Excellence Defence Against Terrorism, Ankara, Turkey (IOS Press, 2013)
Traditionally viewed as a problem affecting the Middle East and South Asia, the threat posed by suicide terrorism is spreading around the globe. The past three years have seen more attacks than the last quarter century. The 9/11 as well as the London attacks have emphasized how acts of suicide terrorism have the potential to cause considerable losses of human lives and damage to physical infrastructure, while influencing the course of the global environment. Thus, in order to develop policies vital to national and international security that will meet the challenges of suicide attacks, the need to understand the causes and the factors involved in this phenomenon appears evident. On the basis of my own experience, and according to the conclusions drawn by well known experts in this field, I have realized that this phenomenon has to be analysed taking three main factors into account: individual, organizational and environmental.